Focus on personal Finance : an active approach to help you develop successful financial skills - Jack R. Kapoor (McGraw Hill Irwin, 2006)
Berisi : Self study dofware, Your personal financial, Online learning center, Personal finance online, Finance around the world. Berupa teks dan link.